2005
DOI: 10.1097/01.aids.0000194128.97640.07
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection and sexually transmitted infections among men who have sex with men in Senegal

Abstract: Men who have sex with men in Senegal are highly infected with HIV and other STI. Intervention programs targeting this population are urgently needed, given their particular vulnerability and because infections are likely to disseminate into the general population given the high proportion of bisexual activity in this community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
138
5
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(165 citation statements)
references
References 18 publications
17
138
5
5
Order By: Relevance
“…This population of men who have sex with men could serve as a potential bridge for HIV transmission to women who ordinarily would be at low risk of infection. Only about half of the men in the study reported using condoms during sex with men or women in the previous month (Wade et al, 2005). (Akwara et al, 2005).…”
Section: Conflict and Hiv Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…This population of men who have sex with men could serve as a potential bridge for HIV transmission to women who ordinarily would be at low risk of infection. Only about half of the men in the study reported using condoms during sex with men or women in the previous month (Wade et al, 2005). (Akwara et al, 2005).…”
Section: Conflict and Hiv Riskmentioning
confidence: 99%
“…However, prevalence remains high in Addis Ababa overall (where it has remained at 14%-16% since the mid-1990s) and in other urban areas (where it has stayed between 11% and 13% in the same period) (Hladik et al, 2006 Research is identifying a previously hidden aspect of the epidemic in Senegal: the role of sex between men as a risk factor for HIV infection. Conducted in five urban areas (Dakar, Kaolack, Mbour, Saint-Louis and Thiés), a study has found HIV prevalence of 22% in men who have sex with men, most of whom (94%) said they also had sex with women (Wade et al, 2005). This population of men who have sex with men could serve as a potential bridge for HIV transmission to women who ordinarily would be at low risk of infection.…”
Section: Conflict and Hiv Riskmentioning
confidence: 99%
“…16 In Africa, the first HIV sero-prevalence survey among MSM was conducted in Senegal in 2005. 13 The study found an HIV prevalence of 21.5% among MSM, compared to 0.2% among adult males overall. 13 Similarly, a survey of MSM in Kenya between 2005-2007 found an HIV prevalence of over 40%, compared to 6.1% among Kenyan adults aged 15-49 years.…”
Section: Mapping Of the Epidemic Among Msm And Key Risk Factorsmentioning
confidence: 82%
“…13 The study found an HIV prevalence of 21.5% among MSM, compared to 0.2% among adult males overall. 13 Similarly, a survey of MSM in Kenya between 2005-2007 found an HIV prevalence of over 40%, compared to 6.1% among Kenyan adults aged 15-49 years. 17 It has been hypothesised that HIV prevalence among MSM in South Africa may also exceed that in the general population 18 but evidence is lacking.…”
Section: Mapping Of the Epidemic Among Msm And Key Risk Factorsmentioning
confidence: 82%
See 1 more Smart Citation